2022
DOI: 10.5588/ijtld.21.0373
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to evaluate a medication monitoring system for TB treatment

Abstract: BACKGROUND: Adherence to TB treatment and therefore treatment success could be improved using digital adherence technology.OBJECTIVE: To evaluate the effectiveness of a medication event reminder monitor system (MERM) on treatment success and treatment adherence in patients with drug-susceptible pulmonary TB in Perú.METHODS: This was an experimental, randomised, open-label, controlled study conducted among patients in the second phase of TB treatment. The intervention group received their medications through M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…On single outcomes by cascade, 11 (12.2%) studies reported TB testing outcomes [ 28 38 ], 22 (23.9%) reported TB diagnosis [ 39 – 57 ], 15 (16.3%) reported on linkage to care [ 58 74 ], 21 (22.8%) studies reported treatment completion [ 11 , 12 , 75 94 ], 9 (9.8%) reported on cure [ 14 , 80 , 95 – 102 ], and 14 (15.2%) studies reported on treatment success [ 80 , 103 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…On single outcomes by cascade, 11 (12.2%) studies reported TB testing outcomes [ 28 38 ], 22 (23.9%) reported TB diagnosis [ 39 – 57 ], 15 (16.3%) reported on linkage to care [ 58 74 ], 21 (22.8%) studies reported treatment completion [ 11 , 12 , 75 94 ], 9 (9.8%) reported on cure [ 14 , 80 , 95 – 102 ], and 14 (15.2%) studies reported on treatment success [ 80 , 103 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reminders have also been explored for improving adherence to tuberculosis treatment in endemic countries. A higher frequency of treatment success was shown in a medication event reminder group (MERM) compared to the traditional directly observed group in one study conducted in Peru [41].…”
Section: Remindersmentioning
confidence: 99%
“…Studies suggest adherence interventions for improving outcomes, such as medication event reminder monitor (MERM) systems, electronic pillboxes, and text messaging [ 10 , 11 ]. Medication reminders appear to improve compliance and staff-patient relationships, but have not been shown to cause significant differences in treatment success [ 12 ].…”
Section: Introductionmentioning
confidence: 99%